2017
DOI: 10.14740/jocmr2915w
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Cardiac Rehabilitation on Visit-to-Visit Variability of Blood Pressure in Patients With Cardiovascular Disease in a 12-Month Follow-Up

Abstract: BackgroundVisit-to-visit variability (VVV) in blood pressure (BP) has been shown to be a strong predictor of cardiovascular disease (CVD). However, the long-term effect of comprehensive cardiac rehabilitation (CR) with exercise training on VVV in BP has not yet been established. Therefore, we evaluated the long-term effects of CR on VVV in BP in patients with CVD.MethodsTwenty-two CVD patients in a 12-month CR program who had at least six clinic visits per month to measure BP were enrolled. We determined VVV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Preliminary findings from a retrospective study indicated that CR reduces all-cause mortality in the approximately 6 yr of follow-up investigation, but the contribution of rehabilitative exercise to risk factor modifications, including BP, was not delineated. Successful control of SBP is nonetheless recognized as essential to long-term cardiovascular health in that CR participation is linked to declines in visit-to-visit SBP 11…”
mentioning
confidence: 99%
“…Preliminary findings from a retrospective study indicated that CR reduces all-cause mortality in the approximately 6 yr of follow-up investigation, but the contribution of rehabilitative exercise to risk factor modifications, including BP, was not delineated. Successful control of SBP is nonetheless recognized as essential to long-term cardiovascular health in that CR participation is linked to declines in visit-to-visit SBP 11…”
mentioning
confidence: 99%